The bioprospecting potential of insect venoms as antibiotics: a mini review - Riva, Henrique G.; Amarillo-S, Angela R. (Frontiers in Microbiology, 2025)
The global rise of antimicrobial resistance has intensified the search for new antibiotic candidates from unconventional biological sources. Insect venoms, although underexplored compared to other venomous taxa, harbor a chemically diverse array of antimicrobial peptides (AMPs) with significant therapeutic promises. This mini review synthesizes evidence from 15 original studies published over the past 15 years that examined the antimicrobial potential of insect venom components. Most investigations have focused on Hymenoptera—wasps, bees, and ants—where peptides such as mastoparans, polydim-I, macropin, melectin, and panurgines that exhibit broad-spectrum activity against multidrug-resistant bacteria while maintaining low toxicity toward mammalian cells. Collectively, these findings highlight insect venoms as a promising resource for antibiotic discovery. Nevertheless, critical challenges remain regarding peptide stability, delivery, pharmacokinetics, and clinical validation. Addressing these gaps through integrative approaches combining molecular, computational, and translational research will be key to advancing insect venom peptides as next-generation anti-infective agents.